2018
DOI: 10.2147/cmar.s179151
|View full text |Cite
|
Sign up to set email alerts
|

ypTNM category combined with AJCC tumor regression grade for screening patients with the worst prognosis after neoadjuvant chemoradiation therapy for locally advanced rectal cancer

Abstract: BackgroundThe purpose of this study was to investigate the value of the postsurgical pathological T and N (ypTN) category combined with the American Joint Committee on Cancer-tumor regression grade (AJCC-TRG) in evaluating the prognosis of neoadjuvant chemoradiation therapy (NeoCRT) for locally advanced rectal cancer (LARC) to screen for a subgroup of patients with the worst prognosis.Patients and methodsIn total, 265 patients with LARC were enrolled in the trial. All patients received NeoCRT. Total mesorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…It is known that the depth of tumor invasion determines the T stage of the tumor and affects adjuvant treatment strategy as well as the postoperative prognosis of a cancer patient. 33 The present study revealed an interesting phenomenon; the classical T stage of the TNM staging system (8th edition) failed to show independent predictive significance in overall patient survival, and tumor size was proven to be an independent predictor in OS analysis. These results are similar to those reported previously.…”
Section: Discussionmentioning
confidence: 54%
“…It is known that the depth of tumor invasion determines the T stage of the tumor and affects adjuvant treatment strategy as well as the postoperative prognosis of a cancer patient. 33 The present study revealed an interesting phenomenon; the classical T stage of the TNM staging system (8th edition) failed to show independent predictive significance in overall patient survival, and tumor size was proven to be an independent predictor in OS analysis. These results are similar to those reported previously.…”
Section: Discussionmentioning
confidence: 54%
“…The observation group received short duration radiotherapy and chemotherapy and the control group received conventional chemoradiotherapy before the operation[ 6 , 7 ]. For the short duration radiotherapy, a total dose of 25 Gy was delivered with 5 Gy daily for 5 d, and the operation was performed within 5 d after the radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods to classify tumor response to nCRT have been evaluated for prognostic significance in LARC patients, each with its own strengths and limitations (9). Histopathologic evaluation of tumor response from the TME specimen by ypTN staging and tumor regression grading (TRG) have been shown to be highly prognostic for LARC patients (6,7,(10)(11)(12)(13). However, the TRG system requires standardization as there are multiple versions describing the proportion of viable residual tumor to fibrosis using different scoring systems (12,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%